Edukasi Pasar Modal Bagi Siswa SMK PGRI 2 Kertosono - Solikah, Mar’atus; Tohari, Amin; Sugeng, Sugeng; Astuti, Puji; Kurniawan, Andy; Puspita, Erna (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
Investment is investing money into an asset to generate profits. Therefore, it is important to start investing early by educating the younger generation about the capital market so that the future is more secure because they have passive income. Capital market education is an effort to provide knowledge about investing in the capital market. The partner in this community service is SMK PGRI 2 Kertosono, Nganjuk Regency. The activity aims to introduce younger students to investing in the capital market. So they can improve their knowledge and investment skills at an early age for future profits. The activities carried out to achieve this goal are socialization methods, active participation of participants, and direct activity assistance by the service team. After the service activity ends, it is hoped that participants will be able to understand the procedures for trading shares in the capital market and how to analyze and know the risks of investing in shares.